Leucism in the three-striped palm squirrel (Funambulus palmarum) at Gudalur Forest Division, Tamil Nadu, Southern India - Samson, Arockianathan; Ramakrishnan, Balasundaram; Bargavi, Subbaiah (THERYA, 2017)
Leucism is a condition characterized by the reduction of all skin pigmentation, generally observed in animals. In this note we describe the first known cases of the leucism in the three-striped palm squirrel in the fragmented forest habitat of Gudalur forest division, Tamil Nadu, Southern India.